Inhibition of Eukaryotic Translation Initiation Factor 5A (eIF5A) Hypusination Suppress p53 Translation and Alters the Association of eIF5A to the Ribosomes - Martella, Marianna (Int J Mol Sci, 2020)
The eukaryotic translation initiation factor 5A (eIF5A) is an essential protein for the viability of the cells whose proposed function is to prevent the stalling of the ribosomes during translation elongation. eIF5A activity requires a unique and functionally essential post-translational modification, the change of a lysine to hypusine. eIF5A is recognized as a promoter of cell proliferation, but it has also been suggested to induce apoptosis. To date, the precise molecular mechanism through which eIF5A affects these processes remains elusive. In the present study, we explored whether eIF5A is involved in controlling the stress-induced expression of the key cellular regulator p53. Our results show that treatment of HCT-116 colon cancer cells with the deoxyhypusine (DHS) inhibitor N1-guanyl-1,7-diamineheptane (GC7) caused both inhibition of eIF5A hypusination and a significant reduction of p53 expression in UV-treated cells, and that eIF5A controls p53 expression at the level of protein synthesis. Furthermore, we show that treatment with GC7 followed by UV-induced stress counteracts the pro-apoptotic process triggered by p53 up-regulation. More in general, the importance of eIF5A in the cellular stress response is illustrated by the finding that exposure to UV light promotes the binding of eIF5A to the ribosomes, whereas UV treatment complemented by the presence of GC7 inhibits such binding, allowing a decrease of de novo synthesis of p53 protein.